Efficacy of ethnobotanical as anthelmintics in the productive performance of darag native chicken - Ozaraga, Ma. Sylvia I. (2014)
The study aimed to evaluate the efficacy of ethnobotanical such as opal-ipil, Betel nut, and papaya seeds as anthelmintics in the productive performance of native chicken. The study used 165 Darag native chickens subjected to a 3X3 factorial experiment in Randomized Complete Block Design (RCBD) with three replications. Two factors were considered: Factor A for the kind of ethnobotanical and Factor B for the dosages (2 g, 4 g, and 6 g/kg bw). Data on the efficacy of the ethnobotanical were obtained by through the percent reduction of roundworm egg per gram (EPG) count before and on the 7th, 14th, 21st, and 28th day post treatment. F-test and least significant difference (LSD), interpreted at 5% and 1% level of significance, were used for statistical analysis.

Results showed a comparable effect in terms of percent reduction of roundworm EPG count on the 28th day post treatment between ethnobotanicals and commercial dewormer (P>0.05). The commercial dewormer showed a higher percent reduction (P<0.01) on EPG count on the 7th day post treatment between the betel nut and ipil-ipil seeds. F-test test revealed that there is a significant difference (P<0.05) on weight gain of the birds in terms of dosage. Birds having the highest dosage of ethnobotanicals had the highest weight gain. There was a highly significant difference in terms of dosage and replication on the feed consumption of birds. F-test showed that the difference between ethnobotanicals and dosage was not significant in terms of feed conversion efficiency. Economic returns showed that all treatments were profitable. The best performance with an average gain of PhP 179.35 was noted from birds treated with ipil-ipil seed powder.
Keywords: Native chicken, Darag